The potentials and obstacles of agricultural development in the district of Koye - Tarq Khidr Hassan (Zanco Journal of Humanity Sciences)
Koye district was chosen as one of the districts of Erbil governorate as a study area because it is an agricultural area, most of its residents depend on agriculture as their main craft, not to mention its location that forms the bridge linking the governorates of Erbil, Sulaymaniyah and Kirkuk with each other, and its proximity to those governorates which are the largest consumer market for agricultural products.